An exploratory study on the collection development efforts of the Ateneo de Manila High School Educational Media Center in adherence to the Enhanced Basic Education Act of 2013 and its prescribed senior high school tracks - Ishihara, Rio Anne A. (2016)
The Philippine Legislature has enacted the Republic Act 10533 or Enhanced Basic Education Act of 2013 as a thrust to strengthen the education system in the country. The main consideration of said Republic Act is to add two (2) more years in basic education, with uniform adjustments on government, public, and private education sectors through adopting a prescribed curriculum.